Shopee Pay Later User Perceptions Of Impulse Buying Behavior - Hasibuan, Laila Kalsum; Siregar, Winda Anriani; Harahap, Abdul Aziz (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The purpose of this study is to see the influence of perceived convenience, perceived benefits, and perceived risk on impulsive buying behavior among students at the Faculty of Economics and Islamic Business, UIN Syekh Ali Hasan Ahmad Addary Padangsidempuan. This study uses a quantitative approach. The results of this research are that simultaneously, convenience, benefits, and risks have a significant effect on impulsive buying behavior. Partially, convenience has a positive and insignificant effect on impulsive buying behavior. Partially, benefits do not have a significant effect on impulsive buying behavior. Partially, risk has a positive and significant effect on impulsive buying behavior.